2020
DOI: 10.3390/molecules25184130
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS-Based Metabolomics for the Chemosystematics of Kenyan Dodonaea viscosa Jacq (Sapindaceae) Populations

Abstract: Dodonaea viscosa Jacq (Sapindaceae) is a medicinal plant with a worldwide distribution. The species has undergone enormous taxonomic changes which caused confusion amongst plant users. In Kenya, for example, two varieties are known to exist based on morphology, i.e., D. viscosa var. viscosa along the coast, and D. viscosa var. angustifolia in the Kenyan inland. These two taxa are recognized as distinct species in some reports. This prompted us to apply metabolomics to understand the relationship among naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Barcoding techniques can further be used in conjunction with metabolomics, transcriptomics or proteomics ( Mishra et al, 2016 ; Raclariu-Manolică et al, 2023b ). The possibility to process data via multivariate analysis, pattern recognition and metabolomics then gives a broader scope for applications in medicinal plant analysis and the spectrum of compounds found within medicinal plants ( Feng et al, 2018 ; Nöst et al, 2019 ; Kaigongi et al, 2020 ; Raclariu-Manolică et al, 2023b ). Modern analytical technologies combined with chemometrics are increasingly used for quality monitoring of medicinal plant matrices, but it is still challenging to choose the adequate type of analysis and statistical method as this is highly dependent on the specific authenticity issue ( Liu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Barcoding techniques can further be used in conjunction with metabolomics, transcriptomics or proteomics ( Mishra et al, 2016 ; Raclariu-Manolică et al, 2023b ). The possibility to process data via multivariate analysis, pattern recognition and metabolomics then gives a broader scope for applications in medicinal plant analysis and the spectrum of compounds found within medicinal plants ( Feng et al, 2018 ; Nöst et al, 2019 ; Kaigongi et al, 2020 ; Raclariu-Manolică et al, 2023b ). Modern analytical technologies combined with chemometrics are increasingly used for quality monitoring of medicinal plant matrices, but it is still challenging to choose the adequate type of analysis and statistical method as this is highly dependent on the specific authenticity issue ( Liu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the compounds putatively identified from mass spectra are based on the literature and databases. It also hinders the absolute quantitation of the detected compounds that were relatively estimated using a few external standards—one for each major phytochemical class [ 35 ]. On the other hand, most of the detected compounds are not available for procurement and are present in minor amounts, which makes the isolation cost-inefficient.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most of the detected compounds are not available for procurement and are present in minor amounts, which makes the isolation cost-inefficient. To overcome this, while still being able to use the data for relative comparisons between phytochemical profiles, one can use various approaches, such as fragmentation patterns [ 35 , 36 , 37 , 38 , 39 , 40 ], supported by a library search (used mainly in the present paper) or coupling (offline) to NMR spectroscopy [ 41 ]. The latter provides much more accurate structural information but is also less affordable and more laborious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 depicts the positive and negative ESI chromatographic profiles for the hydroethanolic extract of D. viscosa leaves. Some chemical constituents in other reports as Isorhamnetin (Al-Snafi, 2017), kaempferol (Omosa et al, 2010), quercetin [24], aliarin (Teffo et al, 2010), methyl dodovisate B (Niu et al, 2010), hardwickiic acid (Niu et al, 2010), fraxetin (Kaigongi et al, 2020), chlorogenic acid (Beshah et al, 2020), p-coumaric acid (Beshah et al, 2020), rutin, viscosol, catechin, and dodonic acid (Kaigongi et al, 2020) were determined by chromatographic analysis and showed antibacterial activity. Otherwise, some compounds in this study have been reported in the first time such as sucrose, quinic acid, shikimic acid, adenosine, N- Frontiers in Pharmacology frontiersin.org Frontiers in Pharmacology frontiersin.org 13…”
Section: Phytochemical Profile By Uplc-esi-ms/msmentioning
confidence: 99%